Prevalence and molecular characterisation of Eimeria species in Ethiopian village chickens - Luu, L.; Bettridge, Judy M.; Christley, Robert M.; Melese, K.; Blake, D.J.H.; Dessie, Tadelle; Wigley, Paul; Desta, T.T.; Hanotte, Olivier H.; Kaiser, P.; Gutu, Z.; Collins, M.; et al. (Springer, 2013)
Background: Coccidiosis, caused by species of the apicomplexan parasite Eimeria, is a major disease of chickens. Eimeria species are present world-wide, and are ubiquitous under intensive farming methods. However, prevalence of Eimeria species is not uniform across production systems. In developing countries such as Ethiopia, a high proportion of chicken production occurs on rural smallholdings (i.e. 'village chicken production’) where infectious diseases constrain productivity and surveillance is low. Coccidiosis is reported to be prevalent in these areas. However, a reliance on oocyst morphology to determine the infecting species may impede accurate diagnosis. Here, we used cross-sectional and longitudinal studies to investigate the prevalence of Eimeria oocyst shedding at two rural sites in the Ethiopian highlands.